CHACARTERIZATION OF LOCAL DURIAN GERMPLASM BASED ON THE MORPHOLOGY OF FRUIT (Sainteknol : Jurnal Sains dan Teknologi, 2016)
One of the efforts to improve the quality and the conservation of local fruits like durian requires characteristic certainty of durian fruits according to the needs of plant breeders and tastes of consumers. Some durian germplasm at Hortimart Agro Center in Central Java have been successfully characterized. There are 43 accessions with 18 characters covering 64 character states of fruit. The dendrogram showed that those 43 accessions split into 2 groups. Durian Kartomarmo separated from the other 42 accessions. Durian Kartosumarmo has a unique characteristic on its fruit, which has an apex with irregular shape (mammiform). Some durians which have good taste, such as durian Bismo, Cokro, Janoko, and Petruk were grouped together with durian Monthong. The coeffient similarity in 43 accessions of the durian fruit is between 0.44-0.86. The diversity of accessions based on the fruit morphology showed that these 43 accessions were different and not a duplicate of different accessions. It shows that each of accession should be categorized as a different cultivar since there are many other characteristics that have not been observed.